2017
DOI: 10.2147/jir.s124947
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of IL-1β, IL-6 and IL-8 cytokines during relapse and remission of idiopathic nephrotic syndrome

Abstract: Background/aimThe role of pro-inflammatory cytokines in the immunopathogenesis of idiopathic nephrotic syndrome had been widely postulated. Reports on the release of cytokines, during idiopathic nephrotic syndrome (INS) activation, were conflicting in defining a specific interleukin pattern during relapse and remission of the disease. The aim of this study was to explore the role of IL-1β, IL-6 and IL-8 in the pathophysiology of INS during relapse and remission.Patients and methodsA total of 37 INS patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“… 25 , 26 Moreover, elevated levels of IL-1β, IL-6, and IL-8 have been reported in the urine samples of 37 children with idiopathic NS during relapse versus remission or healthy controls. 27 Another study of 150 children with idiopathic NS and 569 healthy controls reported significant associations of IL-4, IL-6, and TNF-α polymorphisms between children with NS versus controls, and between SRNS versus SSNS, suggesting that steroid responsiveness may be determined by these polymorphisms. 28 A few other reports have identified cytokines in plasma, urine, and saliva as markers of persistence of proteinuria or SRNS in childhood NS.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 26 Moreover, elevated levels of IL-1β, IL-6, and IL-8 have been reported in the urine samples of 37 children with idiopathic NS during relapse versus remission or healthy controls. 27 Another study of 150 children with idiopathic NS and 569 healthy controls reported significant associations of IL-4, IL-6, and TNF-α polymorphisms between children with NS versus controls, and between SRNS versus SSNS, suggesting that steroid responsiveness may be determined by these polymorphisms. 28 A few other reports have identified cytokines in plasma, urine, and saliva as markers of persistence of proteinuria or SRNS in childhood NS.…”
Section: Discussionmentioning
confidence: 99%
“…TNFα, RANTES) following MMF treatment 32 . Urinary excretion of IL-1β, IL-6, and MCP-1 are elevated in adolescents with idiopathic nephrotic syndrome that also present with impaired renal function and hypertension [33][34][35] . Interestingly, repeated measurements of urinary cytokines have previously been suggested to reflect renal-specific inflammatory signaling in the nephrotic model 34 .…”
Section: Temporal Relationship Of Arterial Pressure and Renal Inflammmentioning
confidence: 99%
“…NOS2 and NOS3, separately encoded the inducible nitric oxide synthase (iNOS) and endothelial nitric oxide synthase (eNOS), are involved in the synthesis of the nitric oxide (NO) and considered as a significant nephroprotective factor [59]. Interleukin, the multifunctional inflammatory cytokines are closely associated with various renal diseases and the injury of kidney residential cells, such as IL-6, CXCL8, IL-1β, IL-2 and IL-4 [60][61][62][63][64]. TNF-α, an important regulatory factor, which can promote the production of IL-6, IL-1β, and other cytokines, participates in inflammation, oxidative stress and damage in various renal diseases [65].…”
Section: Discussionmentioning
confidence: 99%